Perspectives of K. pneumoniae’s zoonotic potential from wild birds to human - Cocoș I. Daiana; Mihai Folescu; Razvan T. Pătrînjan; Larisa Ardelean; Romeo T. Cristina (Medicamentul Veterinar)
Research across various regions demonstrates the prevalence of antimicrobial resistance (AMR) Klebsiella pneumoniae in wild birds, with notable findings including the detection of carbapenemase-producing strains (K. pneumoniae carbapenemase, KPC) in gulls from Spain and Ukraine, and colistin-resistance genes (mcr-1 and mcr-2) in Egyptian migratory waterfowl. Genetic overlaps were observed between avian isolates and human clinical strains, such as indistinguishable K. pneumoniae genomes from grey-crowned cranes in Rwanda and human cases. Migratory species, such as Eurasian Blackcaps in Italy, are implicated as sentinels and reservoirs of AMR genes, facilitating global dissemination. Geographic prevalence studies highlight variability, with 11.5% of birds in Spain harboring carbapenem-resistant phenotypes and 8% prevalence in Italian birds. This review examines the role of wild birds as reservoirs of K. pneumoniae and its implications for AMR and zoonotic transmission. The goal is to synthesize current knowledge on the prevalence, resistance profiles, and potential transmission pathways of K. pneumoniae from avian hosts to humans. Wild birds, including migratory and urban-adapted species, serve as significant reservoirs of AMR genes, potentially transmitting these pathogens to humans through shared environments or migration. The findings underscore the urgent need for a One Health approach to monitor wildlife as part of global AMR surveillance.